CADASIL vs. Multiple Sclerosis: Is It Misdiagnosis or Concomitant? A Case Series - Khan, Ayesha; Abedi, Vida; Li, Jiang; Malik, Muhammad T.; Esch, Megan; Zand, Ramin (Frontiers in Neurology, 2020)
Introduction: Cerebral autosomal dominant arteriopathy and subcortical infarct leukoencephalopathy (CADASIL) is the most common form of hereditary stroke caused by a mutation in the NOTCH3 gene located on the short arm of chromosome 19. A small number of published reports describe cases of CADASIL patients who were initially diagnosed as multiple sclerosis. Although it was previously indicated that there was no association between NOTCH3 mutations and multiple sclerosis, the involvement of autoimmune mechanisms among patients with CADASIL has been hypothesized. Case Presentation: Case 1 is a middle-aged woman with initial diagnoses of multiple sclerosis (MS) and myelitis that continued to progress despite treatment with disease-modifying agents. She had occasional migraines, transient blurred vision, and multiple lacunar infarcts. She continued treatment for about fifteen years with no significant alleviation and progressive changes on brain MRI; genetic testing was ordered which showed positive NOTCH3 results and diagnosis was changed to CADASIL with subsequent revision of treatment course. However, the presence of myelitis in this patient is unusual and may raise the question of a concurrent autoimmune process. Case 2 is a woman presenting with vertigo and paresthesia and diagnosed with MS based on an initial brain MRI showing biventricular white matter hyperintensities; however, she was not started on any disease-modifying agents. Her symptoms were re-evaluated by a neurologist, and genetic testing performed for NOTCH 3. Case 3 is a young woman with a history of migraines who initially presented with numbness and gait ataxia which later progressed to speech difficulty and memory loss. A diagnosis of MS was established which was later changed to CADASIL. Conclusion: Since CADASIL is a rare disease, it is imperative to raise awareness of its unique clinical condition as well as variation in its clinical presentations. It is crucial that the overlapping symptoms between MS and CADASIL be thoroughly examined to avoid misdiagnosis and treatment complications. The involvement of autoimmune mechanisms in CADASIL and the role of NOTCH3 mutations in provoking an autoimmune process should be further investigated.